Synthesis, Evaluation of Cytotoxicity and Molecular Docking Studies of the 7-Acetamido Substituted 2-Aryl-5-bromo-3-trifluoroacetylindoles as Potential Inhibitors of Tubulin Polymerization - Malose J. Mphahlele; Nishal Parbhoo (MDPI AG, 2018)
The 3-trifluoroacetyl–substituted 7-acetamido-2-aryl-5-bromoindoles 5a–h were prepared and evaluated for potential antigrowth effect in vitro against human lung cancer (A549) and cervical cancer (HeLa) cells and for the potential to inhibit tubulin polymerization. The corresponding intermediates, namely, the 3-unsubstituted 7-acetyl-2-aryl-5-bromoindole 2a–d and 7-acetamido-2-aryl-5-bromoindole 4a–d were included in the assays in order to correlate both structural variations and cytotoxicity. No cytotoxicity was observed for compounds 2a–d and their 3-trifluoroacetyl–substituted derivatives 5a–d against both cell lines. The 7-acetamido derivatives 4–d exhibited modest cytotoxicity against both cell lines. All of the 3-trifluoroacetyl–substituted 7-acetamido-2-aryl-5-bromoindoles 5e–h were found to be more active against both cell lines when compared to the chemotherapeutic drug, Melphalan. The most active compound, 5g, induced programmed cell death (apoptosis) in a caspase-dependent manner for both A549 and HeLa cells. Compounds 5e–h were found to significantly inhibit tubulin polymerization against indole-3-carbinol and colchicine as reference standards. Molecular docking of 5g into the colchicine-binding site suggests that the compounds bind to tubulin by different type of interactions including pi-alkyl, amide-pi stacked and alkyl interactions as well as hydrogen bonding with the protein residues to elicit anticancer activity.